2021
DOI: 10.1094/php-07-20-0056-rs
|View full text |Cite
|
Sign up to set email alerts
|

First Report and New Hosts of Pseudofabraea citricarpa Causing Citrus Target Spot in China

Abstract: Citrus target spot, caused by Pseudofabraea citricarpa (Zhu et al.) Chen, Verkley & Crous, was a recently reported disease on satsuma mandarin and kumquat in Chenggu (Shaanxi province, China). In January 2019, target spot-like disease was also observed on ‘Eureka’ lemon and ‘Beijing’ lemon in Wanzhou (Chongqing province), satsuma in Yichang (Hubei province), and ‘Ponkan’ in Jishou (Hunan province). The identity of the causative agent was conducted and confirmed as P. citricarpa based on symptoms, fungal mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…The strains of Pseudofabraea citricarpa used in this study were obtained from field surveys. One strain was obtained from Wanzhou District in Chongqing (30 • 81 ′ N, 108 • 61 ′ E, subtropical monsoon humid zone, annual average temperature of 18.1 • C [24]), while the other was obtained from Chenggu County in Shaanxi Province (33 • 15 ′ N, 107 • 33 ′ E, transition zone between northern subtropical and warm temperate zones, average annual temperature of 14.2 • C, lower than other citrus-producing areas in China [21]) (Figure S1). The affected citrus leaves were sterilized in a sequential manner with 75% ethanol and 5% sodium hypochlorite.…”
Section: Biological Materialsmentioning
confidence: 89%
See 2 more Smart Citations
“…The strains of Pseudofabraea citricarpa used in this study were obtained from field surveys. One strain was obtained from Wanzhou District in Chongqing (30 • 81 ′ N, 108 • 61 ′ E, subtropical monsoon humid zone, annual average temperature of 18.1 • C [24]), while the other was obtained from Chenggu County in Shaanxi Province (33 • 15 ′ N, 107 • 33 ′ E, transition zone between northern subtropical and warm temperate zones, average annual temperature of 14.2 • C, lower than other citrus-producing areas in China [21]) (Figure S1). The affected citrus leaves were sterilized in a sequential manner with 75% ethanol and 5% sodium hypochlorite.…”
Section: Biological Materialsmentioning
confidence: 89%
“…It was described as a disease that thrives in low-temperature conditions [20]. Subsequently, in 2019, citrus target spot was also detected in Wanzhou District (Chongqing), Yichang (Hubei Province) and Jishou (Hunan Province) [21]. Our previous studies have demonstrated the critical role of plant cell wall degradation, plantpathogen protein/polynucleotide interactions, and terpene biosynthesis in the pathogenicity of P. citricarpa [22].…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…), 'Newhall'navel (C.sinensis) orange and Tarocco blood orange (C. sinensis (L.) Osbeck var. Tarrocco) in Chongqing city, et al (Xiao, 2020;Zhan, 2021). Citrus target spot pathogen Pseudofabraea citricarpa will not only infect citrus leaves and branches, but also cause fruits with about 0.5cm-2.2cm brown or black spots.…”
Section: Introductionmentioning
confidence: 99%
“…So far, studies on citrus target spot mainly focused on etiology (Zhu, Wang, 2012;Zhu, 2012;Xiao, 2020;Zhan, 2021), molecular detection (Yang, 2018), prediction of suitable areas (Xu, 2020), resistance identification (Chen, 2022), etc. There were no reports on the disease occurrence dynamics, and there were no effective compound agents, which seriously affects the taken of disease control by plant protection workers.…”
Section: Introductionmentioning
confidence: 99%